Genetic, maternal, and tank determinants of growth in hatchery-reared juvenile Arctic charr ( Salvelinus alpinus ) - March, B. G. E. de (Canadian Journal of Zoology, 1991)
The relative importance of genetic, maternal, and tank effects on the growth of juvenile Arctic charr (Salvelinus alpinus) was examined in an incomplete factorial mating design (4 dams × 4 sires) with stock from the Fraser River, Labrador, Canada. Egg size and hatching success were related only to dams. Mean weights at 30, 75, and 125 days after swim-up, logistic growth curve parameters describing the change in the mean weight, and a measure of condition, all described within families, were significantly related to both dams and sires and were also correlated with each other. The early patterns of significant differences due to dams and sires changed after approximately 125 days. After this time the mean weights in tanks, although still increasing, became negatively correlated with their coefficients of variation (CV), which had changed only slightly with time. The magnitude of the CVs could not be attributed to specific parents. The changed patterns of differences in the means with time suggested that either (i) the social climate within tanks, measured as the CV, affected the growth of all fish even though they were neither crowded nor underfed, or (ii) an individual's ability to grow was dependent not only on its phenotype (initial weight) but also on its genotype, expressed only in data from sibs. These laboratory results may relate to unique distribution and fitness characteristics of natural Arctic charr populations.